Innovative 3D-Bildgebung - Groh, Johannes; Schramm, Simon; Renner, Nina; Krause, J.; Perl, Markus (Die Unfallchirurgie, 2023)
Intraoperative 2D fluoroscopy is often performed for repositioning and implant control. However, this does not always provide the details needed to reliably detect joint steps or incorrect repositioning. Over the last few years, intraoperative 3D imaging has been established and further developed. Multiple studies demonstrate an advantage and better intraoperative control through 3D imaging. Examples are the upper ankle, the proximal tibia and the distal radius; the rates of intraoperative revisions with digital volume tomography (DVT) are between 20–30%. Technical advancements, such as metal artifact reductions, automated plane setting, automated screw detection, and robotic DVT devices, facilitate intraoperative operation, shorten surgical time, and provide improved image quality. By processing the data sets in the form of an immersive, computer-simulated image in terms of “augmented reality” (AR), increased precision can be achieved intraoperatively while reducing radiation exposure. The implementation of these systems is associated with costs, which are offset by cost savings from avoided revisions. Adequate counter-financing is still lacking at the present time. Intraoperative 3D imaging represents an important tool for intraoperative control. The current data situation makes it necessary to address the routine use of 3D procedures, especially in the joint area. The indications are becoming increasingly broader. Technical innovations such as robotics and AR have significantly improved 3D devices in recent years and offer high potential for integration into the OR.
CRIS-Team Scopus Importer:2023-10-27
Keywords: Augmented reality; Digital volume tomography; Intraoperative imaging; Joints; Robotics